Changes in 24‐h energy expenditure, substrate oxidation, and body composition following resistance exercise and a high protein diet via whey protein supplementation in healthy older men - Corbin Griffen; Derek Renshaw; Michael Duncan; Martin O. Weickert; John Hattersley (Physiological Reports, 2022)
Abstract Purpose To investigate changes in 24‐h energy expenditure (EE), substrate oxidation, and body composition following resistance exercise (RE) and a high protein diet via whey protein supplementation (alone and combined) in healthy older men. Methods In a pooled groups analysis, 33 healthy older men [(mean ± SE) age: 67 ± 1 years; BMI: 25.4 ± 0.4 kg/m2] were randomized to either RE (2×/week; n = 17) or non‐exercise (n = 16) and either a high protein diet via whey protein supplementation (PRO, 2 × 25 g whey protein isolate/d; n = 17) or control (CON, 2 × 23.75 g maltodextrin/d; n = 16). An exploratory sub‐analysis was also conducted between RE+CON (n = 8) and RE+PRO (n = 9). At baseline and 12 weeks, participants resided in respiration chambers for measurement of 24‐h EE and substrate oxidation and wore an accelerometer for 7 days for estimation of free‐living EE. Results Resistance exercise resulted in greater increases in fat‐free mass (1.0 ± 0.3 kg), resting metabolic rate [(RMR) 36 ± 14 kcal/d], sedentary EE (60 ± 33 kcal/d), and sleeping metabolic rate [(SMR) 45 ± 7 kcal/d] compared to non‐exercise (p < 0.05); however, RE decreased activity energy expenditure in free‐living (−90 ± 25 kcal/d; p = 0.049) and non‐exercise activity inside the respiration chamber (−1.9 ± 1.1%; p = 0.049). PRO decreased fat mass [(FM) −0.5 ± 0.3 kg], increased overnight protein oxidation (30 ± 6 g/d), and decreased 24‐h protein balance (−20 ± 4 g/d) greater than CON (p < 0.05). RE+PRO decreased FM (−1.0 ± 0.5 kg) greater than RE+CON (p = 0.04). Conclusion Resistance exercise significantly increased RMR, SMR, and sedentary EE in healthy older men, but not total EE. PRO alone and combined with RE decreased FM and aided body weight maintenance. This study was registered at clinicaltrials.gov as NCT03299972.